Feasibility and validity of transcranial duplex sonography in patients with acute stroke. Issue 1 (1st July 2002) - Gerriets, T; Goertler, M; Stolz, E; Postert, T; Sliwka, U; Schlachetzki, F; Seidel, G; Weber, S; Kaps, M
Abstract : Objectives: To evaluate in a prospective multicentre setting the feasibility of transcranial colour coded duplex sonography (TCCS) for examination of the middle cerebral artery (MCA) in patients with acute hemispheric stroke, and to assess the validity of sonographic findings in a subgroup of patients who also had a correlative angiographic examination. Methods: TCCS was performed in 58 consecutive patients within six hours of the onset of a moderate to severe hemispheric stroke. Ultrasound contrast agent (Levovist) was applied if necessary. Thirty two patients also had computed tomography angiography (n=13), magnetic resonance angiography (n=18), or digital subtraction angiography (n=1). In 14 of these patients, both the sonographic and corresponding angiographic examination were performed within six hours of stroke onset (mean time difference between TCCS and angiography 0.8 hours). Eighteen patients, in whom angiography was carried out more than 24 hours after stroke onset, had a follow up TCCS for method comparison (mean time difference 6.1 hours). Results: Initial unenhanced TCCS performed 3.4 (SD 1.2) hours after the onset of symptoms depicted the symptomatic MCA mainstem in 32 patients (55%) (13 occlusions, one stenosis, 18 patent arteries). After signal enhancement, MCA status could be determined in 54 patients (93%) (p<0.05), showing an occlusion in 25, a stenosis in two, and a patent artery in 27 patients. In 31 of the 32 patients who had correlative angiography, TCCS and angiography produced the same diagnosis of the symptomatic MCA (10 occlusions, three stenoses, 18 patent arteries); TCCS was inconclusive in the remaining one. Conclusion: TCCS is a feasible, fast, and valid non-invasive bedside method for evaluating the MCA in an acute stroke setting, particularly when contrast enhancement is applied. It may be a valuable and cost effective alternative to computed tomography and magnetic resonance angiography in future stroke trials.